Evectivity Of Building Permit (Imb) Services At The Department Of Capital Investment And One-Door Integrated Services Of Makassar City - Andi Risma Jaya; Gazali Gazali; Iin Ismayanti; Rusliana Rusliana; Muh Alias (Public Resource Innovation Management and Excellence, 2025)
The service process for granting Building Construction Permits still has many obstacles that are often encountered, including a lack of discipline regarding working hours, for example employees often arrive late, services are complicated and a lack of experts are placed, so that the community as the object or party receiving the service does not feel satisfied. analyzing building permit services at the capital investment office and one-stop integrated services in Makassar City. The type and research design used by the researcher is qualitative descriptive research, which comprehensively describes the effectiveness of the building construction permit granting service at the Makassar City Investment and One-Stop Integrated Services Service. Building permit services at the capital investment and one-stop integrated services service in Makassar City are not yet effective, it can be seen from the procedure which can be said to be complicated because you have to go to the village head and sub-district office to ask for a signature and that can take a long time if the village head or sub-district head is currently outside so the applicant has to wait, in terms of completion time it is also not effective, where the actual time for completing a building permit is 14 working days, but in reality it could take months.